Seroprevalence of hepatitis B and C in Brazilian army conscripts in 2002: a cross-sectional study - Toledo Jr.,Antonio C. (2005)
Hepatitis B and C constitute important public health problems worldwide. In Brazil, studies on prevalence of viral hepatitis have local and regional characteristics; consequently it is difficult to define the national epidemiological situation. Our objective was to evaluate the seroprevalence of hepatitis B and C in conscripts of the Brazilian Army. A transversal study among males aged 17 to 22 years was conducted nationwide. After informed consent, each volunteer filled in a social-behavioral questionnaire and had blood drawn to test for HBsAg and anti-HCV. A total of 7,372 volunteers were evaluated in the second half of 2002. The prevalence of HBsAg was 2.6% (95% confidence interval: 2.2, 3.0) and that of anti-HCV was 1.5% (95% confidence interval: 1.2, 1.8). A wide variation among macro regions and states in the same region was observed for both markers. In conclusion, although this population theoretically had a low risk for HBV and HCV infection, these results are higher than expected for this age range. These findings may indicate a change in the pattern of HBV and HCV transmission in Brazil. Due to the different dynamics of these epidemics, further studies are warranted to confirm these apparent trends.